Correlation of Notions “Democracy”, “Modernization”, “Democratic Transit” - S. A. Velichko (Сибирское юридическое обозрение, 2015)
Correlation of notions “democracy”, “modernization” and “democratic transit” is under study. The author sets forth the fundamentals, compares different modern approaches and assessments of democratic transit theory. The grounds to use the theory of democratic transit in modern history studies are given.